Levels of Psychological Distress of Canadian University Student-Athletes - Sullivan, Philip; Blacker, Mishka; Murphy, Jessica; Cairney, John (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2019)
The mental health of Canadian university students is fairly well researched, but there is relatively little evidence concerning the mental health of Canadian university student-athletes. Recent research in the United States and Canada has suggested that mental health (e.g., anxiety and depression) differs between student-athletes and student non-athletes. However, the results are ambivalent as to whether student-athletes experience more or less psychological distress than their non-athlete peers. To address this gap, the purpose of the current study was to measure the levels of psychological distress in a national sample of 284 university student-athletes. Each athlete completed the Kessler Psychological Distress Scale (K6; Kessler et al., 2002) via a secure online platform. The average score on the K6 for student-athletes was 8.2 out of 24; 19.8% of the sample surpassed the cut-off for assessing the prevalence of severe mental illness. A regression analysis found that gender, starting status, and scholarship status significantly predicted levels of psychological distress. Females, non-starters, and student-athletes without a scholarship were associated with increases in K6 scores.